2019
DOI: 10.1093/milmed/usz224
|View full text |Cite
|
Sign up to set email alerts
|

Helping High School-Aged Military Dependents With Autism Gain Employment Through Project SEARCH + ASD Supports

Abstract: Introduction: Youth with autism spectrum disorder (ASD) face high rates of unemployment, with unique challenges for military-dependent and -connected youth with ASD. This paper reports preliminary findings from Year One of a randomized waitlist controlled trial investigating the efficacy of the Project SEARCH + ASD Supports (PS + ASD) intervention model for military-dependent and -connected youth with ASD. Methods: Treatment group participants (n = 6) participated in internships at a military installation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…In the Wehman 2017 and 2020 studies, intervention participants were more likely to be in open employment, although the proportions varied across the studies (74.2% and 31.6% respectively, compared to 5.6% and 4.8% amongst controls) [65,68]. The outcome was conceptualized differently in Whittenburg et al, wherein the authors found that more intervention recipients accepted job offers for open employment (83.3%) than did participants in the control group (12.5%) [66]. None of the studies with people with autism measured secondary outcomes of interest to this review.…”
Section: Autismmentioning
confidence: 98%
See 4 more Smart Citations
“…In the Wehman 2017 and 2020 studies, intervention participants were more likely to be in open employment, although the proportions varied across the studies (74.2% and 31.6% respectively, compared to 5.6% and 4.8% amongst controls) [65,68]. The outcome was conceptualized differently in Whittenburg et al, wherein the authors found that more intervention recipients accepted job offers for open employment (83.3%) than did participants in the control group (12.5%) [66]. None of the studies with people with autism measured secondary outcomes of interest to this review.…”
Section: Autismmentioning
confidence: 98%
“…Three studies included participants with schizophrenia only [59][60][61], three studies exclusively included individuals with psychosis [62][63][64], and in one study all participants had post-traumatic stress disorder (PTSD) [28]. In the three studies including participants with autism, youth were assessed as having autism with a medical diagnosis of ASD or an educational identification of autism [45,65,66]. Nearly half of the studies included were performed in the USA (n = 12) [27][28][29]45,49,53,55,[59][60][61]65,66].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations